MOTIVASI KERJA BERDASARKAN AYAT-AYAT AL-QURAN TENTANG SEMANGAT DAN KESABARAN - Muhammad Tofiq Effendi; Ferizal; Caryssa Putri; Ribi Tri Amanda; Abelia Gultom; Nazwa Retno; Nova Elsyani; Alika Ramadhani; Siti Sahfina (CV. BAROKAH PUBLISHER, 2026)
This research aims to examine the correlation between work motivation and enthusiasm and patience which are reflected and related in the verses of the Al-Qur'an. Where enthusiasm and patience are urgent values ​​in everyday life, including in the context of work, which can affect productivity and work quality. The background to this research is motivated by the importance of understanding and implementing Islamic values ​​that can be applied in the world of work, to form individuals who are more enthusiastic and patient in facing various life challenges. The aim of this research is to analyze the influence of the Al-Qur'an's teachings about enthusiasm and patience on work motivation. The research method used is literature study with a qualitative approach, namely analyzing and identifying interpretations and interpretations of various verses of the Al-Qur'an related to motivation, enthusiasm and patience at work. The research results show that the verses of the Qur'an which emphasize the importance of trying as hard as possible, maintaining enthusiasm, and being patient in facing tests, have a significant impact on increasing a person's work motivation. However, don't make this enthusiasm for work just an opportunity for worldly pursuits, but balance it with the afterlife and believe that work is worship. Where it is not just about earning a living, but carrying out the obligation to worship Allah SWT. The conclusion of this research is that the integration of the values ​​of enthusiasm and patience in the teachings of the Qur'an can be an effective and efficient source of motivation for individuals at work. Where you believe that all your fortune has been arranged and will not be confused.The implication of the results of this research is the importance of applying the values ​​contained in the Al-Quran and their effects in the work environment to create an atmosphere that supports increased performance, perseverance and patience.